2021
DOI: 10.1001/jamaneurol.2020.3745
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Decompression for Space-Occupying Hemispheric Infarction

Abstract: IMPORTANCEIn patients with space-occupying hemispheric infarction, surgical decompression reduces the risk of death and increases the chance of a favorable outcome. Uncertainties, however, still remain about the benefit of this treatment for specific patient groups.OBJECTIVE To assess whether surgical decompression for space-occupying hemispheric infarction is associated with a reduced risk of death and an increased chance of favorable outcomes, as well as whether this association is modified by patient charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(42 citation statements)
references
References 32 publications
(107 reference statements)
3
32
0
2
Order By: Relevance
“…Thus, there is growing evidence that the incidence of SoT might be underestimated because of a lack of detailed evaluation of subtle neurologic manifestations in the absence of a sinking skin flap. Since DC is increasingly utilized to treat refractory intracranial hypertension for various etiologies, including stroke [28] and traumatic brain injury (TBI) [20], there is an unmet demand for a better understanding of the post-craniectomy related complications.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, there is growing evidence that the incidence of SoT might be underestimated because of a lack of detailed evaluation of subtle neurologic manifestations in the absence of a sinking skin flap. Since DC is increasingly utilized to treat refractory intracranial hypertension for various etiologies, including stroke [28] and traumatic brain injury (TBI) [20], there is an unmet demand for a better understanding of the post-craniectomy related complications.…”
Section: Introductionmentioning
confidence: 99%
“…In relation to men, decompressive craniectomy was lower among the former. Perhaps, partly because of this, the HMI was significantly higher in men with COPD in our study, since surgical decompression has been associated with a decreased chance of death and increased chance of a favorable outcome [ 30 ]. As far as women are concerned, the use of decompressive craniectomy or IHM were not significantly different in both groups.…”
Section: Discussionmentioning
confidence: 97%
“…The IL-1 receptor antagonist, Anakinra, is another potential drug intervention in this context, and has already demonstrated safety and tolerability in marsupial TBI trials (Zhang et al, 2014). Experimental studies have reported that Anakinra is beneficial in wallabies with a combined TBI and tibial fracture (Reinink et al, 2021). This injury combination results in exacerbated neuroinflammation compared to an isolated TBI (Wickwire et al, 2018), and may bear similarities to what would occur in a combined TBI and T. gondii setting.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%